Digital divide in ASEAN member states: analyzing the critical factors for successful e-government programs - Apriliyanti, Indri Dwi; Kusumasari, Bevaola; Pramusinto, Agus; Setianto, Widodo Agus (2021)
Purpose: This study addresses the critical factors that contribute to the success of e-government programs in the Association of Southeast Asian Nations (ASEAN) member states (AMS). We investigate the factors that play key roles in e-government adoption and implementation in AMS that stem from multiple dimensions. Design/methodology/approach: Our qualitative study on eight ASEAN countries with different political situations and economic developments suggests that in general, institutions (formal and informal institutions), resources, leadership, organizational design and culture values determine the success of e-government. Findings: The provision of adequate information and communication technology infrastructure alone is insufficient to ensure the success of e-government. Research limitations/implications: Our findings lead to a conceptual framework of factors that drive the success of e-government projects that advances the literature on e-government, particularly the research about e-government in the context of developing countries. Originality/value: An empirical evidence and in-depth understanding suggest that different factors are associated with detrimental impacts on e-government implementation. © 2020, Emerald Publishing Limited.